ANALISIS STRUKTUR TIPE WARREN UNTUK RANGKA ATAS JEMBATAN (STUDI KASUS: JEMBATAN KOTO ILALANG, BASO) - Ridha Sari; Sutria Desman; Hanifah Asnur (Ensiklopedia of Journal, 2021)
The bridge structure calculation should be carried out in detail and thoroughly. Like any other civil buildings, bridges involve the livelihood of many people. So that a small mistake in planning can be fatal. The Air Koto Ilalang Bridge, which is located on the border of Payakumbuh – Baso, has an important role in connecting Bukittinggi, Limapuluh Kota and Payakumbuh as well as being part of the main connecting route between West Sumatra Province and Riau. Built in 1980, this bridge took a reconstruction in 2020. In this study, an analysis was carried out on the superstructure of the Koto Ilalang bridge with warren type of structure ; loading analysis, calculation of reinforcement for floor plates and the sidewalks, calculating the profile of the transverse girder and the main girder of the bridge. The results show that the bridge floor plate thickness is 30 cm. And the dimensions of the reinforcement on the floor slab are reinforcement 16 – 200 mm at the pedestal and the field. For stringers and transverse girders, steel structure profiles are used IWF 582.300.12.17 as stringers, IWF 900.300.16.28 as transverse girders, IWF 428.407.20.35 as main girders. Meanwhile, the deflection control obtained a value of 1.1224 cm, where this figure is still within the safe limit because the allowable deflection limit is 9 cm.Keywords: Steel, Bridge, Warren Trus, Stringer